Optimization of hydrolysis conditions for the production of shrimp protein hydrolysate by using Protamex: effect of pH and temperature / Nuramalina Ab. Aziz. - Ab. Aziz, Nuramalina (2009)
Studies on optimization of hydrolysis conditions for the production of shrimp protein hydrolysate by using Protamex™ were descibed. Shrimp protein hydrolysate was prepared from shrimp meat. The hydrolysates treated bv Protamex™ for 120 minutes and enzyme termination was done by heat inactivation at 80 C for 10 minutes. Hydrolysis conditions (pH and temperature) for preparing shrimp protein hydrolysates from the shrimp meat were optimized by response surface methodology (RSM) using a central composite design (CCD). Model equation was proposed with regard to the effect of pH and temperature on the nitrogen recovery (NR) and degree of hydrolysis (DH). A pH 6.46 and temperature of 55.14 C were found to be the optimum conditions to obtain a higher degree of hydrolysis while optimum conditions for nitrogen recovery were pH 7.47 and temperature 55.11°C. Statistical analysis of results showed that nitrogen recovery ranged from 0.91 to 3.73% while degree of hydrolysis ranged from 0.74 to 3.71%.